1987
DOI: 10.1111/j.1469-8749.1987.tb02486.x
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of a ‘Buddy’ Programme to Improve Children's Attitudes Toward the Disabled

Abstract: SUMMARY Children's attitudes to their disabled peers exert a powerful influence on the process of integration of the disabled. This study reports a randomized controlled trial of a ‘buddy’ interaction programme in which gender‐matched able‐bodied and disabled schoolmates were paired over a three‐month period. 43 per cent of the buddy children had a significant improvement in attitudes, compared with 18 per cent of the controls. Buddies also got to know significantly more disabled schoolmates than did the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
3
3

Year Published

1991
1991
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 17 publications
2
24
3
3
Order By: Relevance
“…3,45,51,53,65-2 instruments Responsiveness was not formally described for any of the instruments. However, four instruments were used in intervention studies [55][56][57][58][59] (Table II) with pretest and posttest measures.…”
Section: Psychometric Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…3,45,51,53,65-2 instruments Responsiveness was not formally described for any of the instruments. However, four instruments were used in intervention studies [55][56][57][58][59] (Table II) with pretest and posttest measures.…”
Section: Psychometric Propertiesmentioning
confidence: 99%
“…The effectiveness of a given intervention may be assessed by measuring attitudes before and after the implementation of the intervention. This type of methodology was employed in five studies [55][56][57][58][59] using four different instruments (Acceptance Scale, CATCH, PATHS, and Personal Attribute Inventory for Children). The interventions used in those studies focused mainly on direct contact between children with disabilities and their peers, which was considered as the most effective technique to modify attitudes towards peers with disabilities.…”
Section: Review 187mentioning
confidence: 99%
“…Cabe reseñar la tendencia general de los estudios analizados a mostrar mejores actitudes por parte de las chicas (Armstrong, Rousenbaum, & King, 1987;Hutzler et al, 2007;Liu, Kudláček, & Ješina, 2010;Reina, López, Jiménez, García Calvo, & Hutzler, 2011;Slininger et al, 2000;Xafopoulos et al, 2009).…”
Section: Resultados De Los Estudiosunclassified
“…Armstrong et al (1987) afirmaron en su estudio que el 17% de la muestra mostró un descenso en las puntuaciones del postest. Por su parte, Hutzler et al (2007) encontraron un descenso significativo en las puntuaciones de las chicas en la subescala afectiva.…”
Section: Resultados De Los Estudiosunclassified
“…What would have been interesting -and what should be pursued in future attitudes research -is to explore whether, as we found, changes in children's attitudes are mirrored by changes in parents' attitudes. 4 Were this to be found in other studies it would enhance the argument in favour of experiential learning about differences being an integral part of the fabric of schoolaged children's curriculum. Qualitative exploration of the nature and mechanisms of such child-to-parent transmission would also provide fascinating new insights into social learning.…”
mentioning
confidence: 97%